2015
DOI: 10.1186/1687-9856-2015-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased height standard deviation scores in response to growth hormone therapy to near-adult height in older children with delayed skeletal maturation: results from the ANSWER Program

Abstract: BackgroundA primary goal of recombinant human growth hormone therapy (GHT) in children is attaining normal adult height. In this study, children with growth hormone deficiency (GHD) (including isolated idiopathic growth hormone deficiency [IGHD] and multiple pituitary hormone deficiency [MPHD]), idiopathic short stature (ISS), and Turner syndrome (TS) were evaluated for near-adult height (NAH) and percent achieving NAH within the normal range after approximately 4 years of GHT.MethodsData from the American Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…We identified appropriate segregants by genotyping and then used chemostat competition experiments to determine the independent fitness effects of each evolved mutation ( Fig 2 and S2 Table ). More than half of the mutations examined showed either neutral/near-neutral (<5%) fitness increase or negative effects on fitness, agreeing with previous reports that genetic hitchhiking is quite important for the spectrum of mutations observed in asexually evolving populations [ 33 , 34 ]. In particular, the supernumerary chromosome isolated from evolved clone S8c2, despite occupying 13% of the S8 population, actually decreased the fitness of clones carrying it by 10% ( Fig 2 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We identified appropriate segregants by genotyping and then used chemostat competition experiments to determine the independent fitness effects of each evolved mutation ( Fig 2 and S2 Table ). More than half of the mutations examined showed either neutral/near-neutral (<5%) fitness increase or negative effects on fitness, agreeing with previous reports that genetic hitchhiking is quite important for the spectrum of mutations observed in asexually evolving populations [ 33 , 34 ]. In particular, the supernumerary chromosome isolated from evolved clone S8c2, despite occupying 13% of the S8 population, actually decreased the fitness of clones carrying it by 10% ( Fig 2 ).…”
Section: Resultssupporting
confidence: 90%
“…Second, we expected there to be fewer suppressor mutations, which are commonly selected for in a homozygous or haploid deletion background to ameliorate the effects of the deleted gene [ 41 , 42 ]. Importantly, we were only able to take advantage of the yeast heterozygous deletion collection in this way because our lab had previously determined a set of 2,254 strains from this collection that have neutral fitness, with a range of relative fitnesses from -0.05 to 0.04, under our standard chemostat growth conditions of sulfate-, glucose-, and phosphate-limitation ( S4 Table ) [ 34 ]. Thus, by restricting our method to these 2,254 deletion collection strains and the limitations under which they have neutral fitness, we can be reasonably confident that any fitness effects we do measure are due to the Tamp itself and not the underlying genetic background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of prospective/retrospective, randomized/non-randomized, and controlled/ non-controlled trials, some researchers concluded that GH treatment improved ISS while others considered it ineffective. The efficacies in these studies varied dramatically [12][13][14][15][16][17][18]. Some meta-analyses showed that GHtreated ISS patients might gain more FAH than untreated children, but were still shorter than the normal populations.…”
Section: Discussionmentioning
confidence: 99%
“…Height standard deviation score (HtSDS) = (actual height − average height for children of the same sex and age) ÷ (SD of the heights for children of the same sex and age) [11]. TH (i.e., mid-parental target height) was as follows: FAH was defined as follows: age at the last follow-up was > 15 years, height velocity was below 1 cm/year, and the GH therapy had been discontinued [12].…”
Section: Methodsmentioning
confidence: 99%